Phase Compositions and Microwave Dielectric Properties of Na1+xSrB5O9+0.5x Ceramics - Xuepeng Lu; Peng Wu; Huimin Yang; Min Yang; Yong Zheng (Crystals, 2023)
Microwave dielectric ceramics composed of Na1+xSrB5O9+0.5x (0 ≤ x ≤ 0.125) were synthesized via a traditional solid-state reaction approach. The effects of non-stoichiometric Na on the crystal structures, phase compositions, chemical bond characteristics, and microwave dielectric properties of the Na1+xSrB5O9+0.5x ceramics were systematically studied. All Na1+xSrB5O9+0.5x ceramics sintered at optimum temperatures consisted of a NaSrB5O9 solid-solution phase and a SrB2O4 phase. Appropriate excess Na could suppress the generation of the SrB2O4 phase, and the lowest content of the SrB2O4 phase was achieved at x = 0.075. The εr values of the Na1+xSrB5O9+0.5x ceramics were primarily affected by the relative density and molecular polarization. The Q × f values showed a positive correlation with the lattice energy. The τf value was correlated to the SrB2O4 phase content, bond valence, and bond energy. Typically, the Na1.075SrB5O9.0375 ceramic sintered at 825 °C possessed good microwave dielectric properties of εr = 5.61, Q × f = 31, 937 GHz, and τf = −3.09 ppm/°C, which are suitable for high-frequency, low-temperature co-fired ceramics (LTCCs) substrate applications.